Troubleshooting rotating machinery : including centrifugal pumps and compressors, reciprocating pumps and compressors, fans, steam turbines, electric motors, and more - Perez, Robert X.; Conkey, Andrew P. (Wiley ; Scrivener Publishing, 2016)
Process machines are critical to the profitability of processes. Safe, efficient and reliable machines are required to maintain dependable manufacturing processes that can create saleable, on-spec product on time, and at the desired production rate. As the wards of process machinery, we wish to keep our equipment in serviceable condition. One of the most challenging aspects of a machinery professional or operator's job is deciding whether an operating machine should be shut down due to a perceived problem or be allowed to keep operating. If he or she wrongly recommends a repair be conducted, the remaining useful machine life is wasted, but if he or she is right, they can save the organization from severe consequences, such as product releases, fires, costly secondary machine damage, etc. This economic balancing act is at the heart of all machinery assessments. Troubleshooting is part science and part art. Simple troubleshooting tables or decision trees are rarely effective in solving complex, real-world machine problems. For this reason, the authors want to offer a novel way to attack machinery issues that can adversely affect the reliability and efficiency of your plant processes. The methodology presented in this book is not a rigid "cook book" approach but rather a flexible and dynamic process aimed at exploring process plant machines holistically, in order uncover the true nature the problem at hand